2018
DOI: 10.1007/s40995-018-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Magneto-structural Properties and Colloidal Stability Studies of Ni0.3Zn0.7Fe2O4 Nanoparticles Coated with Pluronic P123 Block Copolymer for Potential Biomedical Applications

Abstract: Spinel Ni 0.3 Zn 0.7 Fe 2 O 4 (NZFO) magnetic nanoparticles was prepared by the low temperature auto-combustion method using a glycine fuel-rich composition without any further heat treatment at high temperature. Subsequently, the synthesized MNPs were coated with Pluronic P123 (PP123) after its surface was functionalized with oleic acid (OA). The effect of the coatings on the morphology, structural and magnetic properties of NZFO nanoparticles was studied using powder X-ray diffraction (XRD), Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The ionized hydroxyl groups of PEG 400 and poloxamer 407 contribute to the negative surface charge of the nanocurcumin. Our results suggest that PEG and poloxamer-coated nanocurcumin is stable and suitable for use in biomedical applications [ 35 ]. Related studies have also reported the spherical shape of curcumin-loaded phospholipid-based nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The ionized hydroxyl groups of PEG 400 and poloxamer 407 contribute to the negative surface charge of the nanocurcumin. Our results suggest that PEG and poloxamer-coated nanocurcumin is stable and suitable for use in biomedical applications [ 35 ]. Related studies have also reported the spherical shape of curcumin-loaded phospholipid-based nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Mn 0.2 Zn 0.8 Fe 2 O 4 , Mn 0.5 Zn 0.5 Fe 2 O 4 and Mn 0.8 Zn 0.2 Fe 2 O 4 -nanoparticles [134]. Analogously, Ehi-Eromosele et al have prepared pluronic P123 molecules coated with mixed SPF-Ni 0.3 Zn 0.7 Fe 2 O 4 -nanoparticles (after initial functionalization with OA molecules), that have revealed improved stability at a physiological pH of 7.4-attributed to a high zeta potential value [135].…”
Section: Spf Nanoparticle-based Mnpsmentioning
confidence: 93%
“… 64 Ehi-Eromosele et al investigated the colloidal stability of Co 0.8 Mg 0.2 Fe 2 O 4 and demonstrated that, as crystallite size increased after PEG coating, some of the smaller particles may have joined together to form larger particles, which is consistent with the current study. 65 …”
Section: Methodsmentioning
confidence: 99%
“…64 Ehi-Eromosele et al investigated the colloidal stability of Co 0.8 Mg 0.2 Fe 2 O 4 and demonstrated that, as crystallite size increased after PEG coating, some of the smaller particles may have joined together to form larger particles, which is consistent with the current study. 65 The structural parameters such as crystallite size, lattice constant (a), cell volume (V), X-ray density (d x ) and hopping lengths (L) were calculated using the formulas from the literature. 66 All calculations use the d spacing values and the corresponding (hkl) lattice parameters, and Table 1 summarizes the structural parameters for the NPs.…”
Section: ■ Introductionmentioning
confidence: 99%